RESEARCH TOPIC: PROMOTING CULTURAL DIVERSITY AND INCLUSIVITY IN CROSS-BORDER MUSIC PRACTICE PROGRAMS IN VOCATIONAL COLLEGES - Ting Qi (Fonseca, Journal of Communication, 2024)
This research is a systemic review of literature on the music practices in cross-border vocational colleges and they are open for cultural diversity and inclusivity. It covers the integration of cultural authentic education, effects of technology and digitization, personalized learning, and educational strategies that promote equity, inclusion, and student motivation. The study reveals how important is to place music education in the context of a multicultural student body, use digital media that allows for greater access and engagement, and design education to correspond with the professional profiles of each student. It also gives the attention to equity and inclusion as a way of building supportive learning environments and the role of pedagogical innovation and teacher training as means of enhancing quality and effectiveness of music education. These results emphasize the necessity of integrated strategies to eliminate Eurocentric biases, language barriers and power balance in the way to inclusivity. Suggestions have been made to integrate intercultural competence training, incorporating diversity in curricula, addressing language barriers, promoting equality and inclusion, creating collaborative environments, and providing supportive institution settings. The significance of transnational music programs in vocational colleges is highlighted on the ground that they empower students with the competencies, know-how and attitudes required for the success in the newly emerging, culturally diverse community.